1998
DOI: 10.1021/jf9801522
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Glycosides from the Seed Coat of a New Manteca-Type Dry Bean (Phaseolus vulgaris L.)

Abstract: Two flavonol glycosides were isolated from the methanol extracts of “Prim”, a variety of Phaseolus vulgaris L. (Manteca-type), with a yellow seed coat color. High-performance liquid chromatography was used to isolate and identify compound 1, kaempferol (3,4,5,4‘-tetrahydroxyflavone)-3-O-β-d-glucopyranoside, and compound 2, kaempferol 3-O-β-d-glucopyranoside-(2→1)-O-β-d-xylopyranoside. Concentrations of these compounds were 49.9 ± 0.78 mg/100 g and 58.5 ± 1.67 mg/100 g of fresh whole bean weight, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…However, interestingly in the tannin containing lentils, there are approximately equal amounts of catechin and gallocatechin, and separately also epicatechin and epigallocatechin (Elessawy et al, unpublished data, 2019), whereas the pea samples contain ?100 times more gallocatechin compared with catechin (and epigallocatechin compared with epicatechin), suggesting that for purple flower pea, the pathway through F3¢5¢H is strongly favored over DFR. Similar to our results, several researchers reported accumulation of flavonoid intermediates in unpigmented seed coats of various crops, such as Brassica carinata A. Braun (Marles et al, 2003), Vicia faba cultivar Blandine (Bekkara et al, 1998), and a manteca-type common bean cultivar Prim (Beninger et al, 1998). Hart et al (2015) tested the effect on Fe bioavailability of the eight most abundant polyphenols present in black bean seed coats using Caco-2 cells (human cell line) and found that four polyphenols (myricetin, myricetin 3-glucoside, quercetin, and quercetin 3-glucoside) inhibited Fe uptake by the CaCo-2 cells.…”
Section: Comparison Of Polyphenolic Profile In Pea With Lentil and Otsupporting
confidence: 92%
“…However, interestingly in the tannin containing lentils, there are approximately equal amounts of catechin and gallocatechin, and separately also epicatechin and epigallocatechin (Elessawy et al, unpublished data, 2019), whereas the pea samples contain ?100 times more gallocatechin compared with catechin (and epigallocatechin compared with epicatechin), suggesting that for purple flower pea, the pathway through F3¢5¢H is strongly favored over DFR. Similar to our results, several researchers reported accumulation of flavonoid intermediates in unpigmented seed coats of various crops, such as Brassica carinata A. Braun (Marles et al, 2003), Vicia faba cultivar Blandine (Bekkara et al, 1998), and a manteca-type common bean cultivar Prim (Beninger et al, 1998). Hart et al (2015) tested the effect on Fe bioavailability of the eight most abundant polyphenols present in black bean seed coats using Caco-2 cells (human cell line) and found that four polyphenols (myricetin, myricetin 3-glucoside, quercetin, and quercetin 3-glucoside) inhibited Fe uptake by the CaCo-2 cells.…”
Section: Comparison Of Polyphenolic Profile In Pea With Lentil and Otsupporting
confidence: 92%
“…The identification of compound 2 was confirmed by the injection of authentic standard and by comparison of their retention times and spectral data. These findings were in agreement with several literature data reporting the presence of kaempferol 3-O-glucoside [22,23,36,37] and kaempferol 3-acetylglucoside [22] in various Phaseolus genotypes.…”
Section: Identification Of Functional Compounds In Selected Accessionssupporting
confidence: 93%
“…Seeds of bambara groundnuts exhibit a high phenotypic diversity and selection of varieties for cultivation usually depends on seed coat colour and pattern. Seed coat colour is attributed to the presence and amount of phenolic derivatives [8] [9], which have been reported to have antimicrobial activity [10], and disease resistance [11] [12]. Disease and pest resistance and high yield are some requirements of commercial farmers.…”
Section: Introductionmentioning
confidence: 99%